Long-term effects of childhood abuse on mental health and delinquent behavior in adulthood: A systematic review - Puente-Ortega, Thaís; Moreta-Herrera, Rodrigo; Torales, Julio (Medicina Clínica y Social, 2025)
Introduction: This research examines the long-term effects of childhood abuse on adult mental health and delinquent behavior. Methods: A systematic review was conducted following PRISMA guidelines. From 500 studies initially identified, 100 duplicates were removed. Titles and abstracts were screened, excluding studies that did not meet inclusion criteria, such as non-systematic reviews or those lacking relevant data. Fifty studies underwent full-text review, and 25 met the final inclusion criteria. Results: A significant association was found between childhood abuse and adult mental health disorders, including anxiety, depression, and personality disorders. Moreover, childhood abuse was strongly linked to adult involvement in both violent and non-violent crimes. Conclusions: The evidence highlights the long-term impact of childhood abuse on mental health and delinquent behavior, emphasizing the need for focused research within specific national contexts.
Keywords: Childhood abuse; mental health; delinquent behavior; systematic review; long-term impact